Pengaruh Risiko Kredit dan Kecukupan Modal Terhadap Profitabilitas - Munggar, Puspa Widyadari; Nurhasanah, Nunung; Kosasih, Kosasih (Gorontalo Accounting Journal, 2024)
This research aims to determine the effect of credit risk and capital adequacy on profitability in state-owned banking companies. This research method uses quantitative methods with multiple regression analysis. The results of the research show that credit risk has a negative and significant effect on profitability, with a negative regression coefficient of -0.531 and a significance value of 0.002 0.05. Meanwhile, capital adequacy has a positive and significant effect on profitability, with a positive regression coefficient of 0.317 and a significance value of 0.001 0.05. Credit Risk and Capital Adequacy have a significant effect on Profitability with an R Square value of 71.1%.